Assessment of prevalence and monitoring of outcomes in patients with heart failure in Russia - E. V. Shlyakhto; N. E. Zvartau; S. V. Villevalde; A. N. Yakovlev; A. E. Soloveva; A. A. Fedorenko; V. A. Karlina; N. G. Avdonina; G. V. Endubaeva; V. V. Zaitsev; G. A. Neplyueva; E. I. Pavlyuk; et al. (Российский кардиологический журнал, 2020)
The increasing prevalence of heart failure (HF) serves as a reverse side of the effective treatment for cardiovascular diseases (CVD) and increasing patient survival. Data on the epidemiology of HF and related mortality in Russia are limited. According to the EPOCHA trial (hospital phase), the prevalence of HF in the Russian Federation is 7%. HF can significantly contribute to cardiovascular mortality. However, its recognition is limited by the peculiarities of the mortality coding system in Russia. The article presents the authors’ view on the registration of HF-related morbidity and mortality cases and perspectives of using left ventricular ejection fraction <50% for statistical reporting.